Early Immune Function and Duration of Organ Dysfunction in Critically Ill Children with Sepsis - Muszynski, Jennifer A; Ramilo, Octavio; Hall, Mark W; Nofziger, Ryan; Moore-Clingenpeel, Melissa; Greathouse, Kristin; Anglim, Larissa; Steele, Lisa; Hensley, Josey; Hanson-Huber, Lisa; Nateri, Jyotsna (American journal of respiratory and critical care medicine, 2018)
Because an intact immune response is important to help clear initial infection, prevent secondary infection, and prevent latent virus reactivation, immune function is likely highly relevant in sepsis. Healthy children were excluded if they had subjective or measured fever within the past 24 hours, history of systemic corticosteroid use within the past month, aspirin or nonsteroidal antiinflammatory drug use in the past 48 hours, or a history of a chronic inflammatory disease, malignancy, or transplantation. Because our previous studies indicate that immune suppression in critical illness occurs across multiple diagnoses and is not limited to sepsis, we chose to compare children with sepsis to healthy children rather than ICU control subjects (5-7). [...]innate immune cells (e.g., monocytes) play a central role in early host defense, whereas adaptive immune cells (e.g., lymphocytes) are responsible for longer-term immunologic modulation. [...]early reductions in innate and adaptive immune function as measured by ex vivo stimulated cytokine production assays were associated with prolonged organ dysfunction in this cohort of critically ill children with sepsis.